The Impact of Human Capital on Fertility: Evidence from Asia and Africa - Bin-Milud, Ahmed (Université d'Ottawa | University of Ottawa, 2018)
This study analyzed the impact of human capital on fertility in Asia and Africa. Although Asia and Africa have relatively lower human capital and a higher fertility rate compared to other regions, the empirical findings show that the impact of human capital on fertility is negative and significant for the whole sample. However, compared to Africa, the impact of human capital on fertility is even lower in Asia--which indicates that there is a higher impact of an increase in human capital on fertility in the case of Asia. Despite very low human capital and a higher fertility rate in both of these regions, the link between the two factors does exist in these regions and therefore there is a need to increase investment in human capital in order to control the fertility rate.